2018
DOI: 10.21276/apalm.1970
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of p53 Expression in Colorectal Adenocarcinomas and its Clinicopathological Correlation

Abstract: Background: Colorectal carcinoma is the fourth most frequent cancer in men and the third in women worldwide. The identification of molecular markers that have a prognostic significance in colorectal carcinoma may have an impact on its treatment. This study aims to identify and evaluate the immunohistochemical expression of p53 in colorectal adenocarcinomas and to correlate its expression with various clinicopathological parameters. Methods:The present study was an observational study done in 30 surgical resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Further studies have shown that p53 did not correlate to clinicopathological characteristics (23,26). Inversely, the Indian study found that p53 staining was significantly associated with histologic types, grade, tumor location, T4 stage and lymph node metastasis (37). Also, other study demonstrated a significant correlation between positive p53 and differentiation, tumor size, pTNM stage, nerve invasion and vessel invasion (17).…”
Section: Correlation Between P53 Bcl-2 Bcl-xl and Ecadherin Expressio...mentioning
confidence: 95%
“…Further studies have shown that p53 did not correlate to clinicopathological characteristics (23,26). Inversely, the Indian study found that p53 staining was significantly associated with histologic types, grade, tumor location, T4 stage and lymph node metastasis (37). Also, other study demonstrated a significant correlation between positive p53 and differentiation, tumor size, pTNM stage, nerve invasion and vessel invasion (17).…”
Section: Correlation Between P53 Bcl-2 Bcl-xl and Ecadherin Expressio...mentioning
confidence: 95%